2011
DOI: 10.1177/1545968310394871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment Intensity in Upper Limb Robot-Assisted Therapy for Chronic Stroke

Abstract: Higher intensity of RT that assists forearm and wrist movements may lead to greater improvement in motor ability and functional performance in stroke patients. A sample size of only 20 to 25 in each arm of a larger randomized controlled trial is needed to confirm the findings for similar subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 55 publications
4
85
1
2
Order By: Relevance
“…704,705 Overall, robotic therapy appears to provide some benefit for upper extremity motor abilities and participation but is of uncertain utility compared with dose-matched conventional upper limb exercise therapies. [706][707][708][709][710][711][712][713] NMES can be used for those with minimal ability for volitional muscle activation. It may be beneficial for improving upper extremity activity if used in combination with taskspecific training, particularly when applied to the wrist and hand muscles.…”
Section: Iib Bmentioning
confidence: 99%
“…704,705 Overall, robotic therapy appears to provide some benefit for upper extremity motor abilities and participation but is of uncertain utility compared with dose-matched conventional upper limb exercise therapies. [706][707][708][709][710][711][712][713] NMES can be used for those with minimal ability for volitional muscle activation. It may be beneficial for improving upper extremity activity if used in combination with taskspecific training, particularly when applied to the wrist and hand muscles.…”
Section: Iib Bmentioning
confidence: 99%
“…Several groups are studying the function of treatment intensity in upper limb rehabilitation, the preliminary results (pilot study) of which have shown that higher intensity robotic treatment (assisted forearm and wrist movements) affects greater improvements in motor ability and functional performance in stroke patients [69]. Higher intensity of robotic rehabilitation in acute phase appears to induce more substantial improvements than lower intensity treatments at discharge, but this difference does not remain after 6 months [70].…”
Section: Lower and Upper Limbmentioning
confidence: 99%
“…Patients in the higher-intensity RT received twice the number of the repetitions per unit of time than patients in the lower-intensity RT group. 15 Before the RT training, 5 minutes of mobilization warm-up were provided. After the training, the patients received 15 to 20 minutes of functional activities practice to help them transfer the acquired motor ability to their performance of daily activities.…”
Section: Interventionsmentioning
confidence: 99%